Students’ experiences using AI as a learning assistant in online education: A phenomenological study - Kenny Candra Pradana (Interdisiplinary Journal of Pedagogy and Research in Media Technology, 2025)
Background: The rapid development of Artificial Intelligence has reshaped online learning environments by offering instant explanations, personalized support, and automated feedback. Although AI tools are increasingly integrated into higher education, limited research has examined students’ subjective experiences, especially within fully online learning contexts where dependence on digital tools is higher.Aims:This study aims to explore students’ lived experiences in using AI as a learning assistant during online education and to identify the benefits, challenges, and ethical concerns arising from this interaction.Methods: A qualitative phenomenological design was employed to capture the meaning behind students’ experiences. Participants were undergraduate students who had used AI tools for at least three months. Data were collected through semi structured online interviews and analyzed using Interpretative Phenomenological Analysis to identify key themes.Result: The study revealed four major themes. Students perceived AI as a practical and supportive learning companion that enhanced comprehension and reduced learning anxiety. However, limitations related to inaccurate information required students to verify AI outputs and develop stronger digital literacy. AI also influenced self regulation by helping students plan and monitor their learning, though concerns regarding overreliance were noted. Ethical uncertainties about plagiarism and unclear institutional guidelines further shaped students’ experiences.Conclusion: AI has significant potential to enrich online learning when used thoughtfully and responsibly. To maximize benefits and reduce risks, institutions should provide clear policies, strengthen students’ digital literacy, and offer ethical guidance for AI use in academic tasks.